The "uncensored war" : the media and Vietnam - Hallin, Daniel C. (Oxford University Press, 1986)
This book is the first scholarly study of Vietnam news coverage, and shows how Kennedy and Johnson both tried to discourage press coverage, and how relations between the press and the Nixon administration completely broke down.